(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
The aim of this paper is to investigate the effect of woven construction and tension of warp and weft in the woven fabric on the seam slippage using a new approach with video analysis. The method includes measuring the surface of the resulting hole after subjecting the samples to seam slippage test, described in standard HRN EN ISO 13936-1:2008. The new method provides a more detailed and broader description of seam damage caused by tensile stress. Testing was also conducted using the standard method by measuring the distance two adjacent threads. The results show that surface of resulting “hole” depends on the density of warp and weft and the weave of the fabric. The new approach enables a detailed overview of the seam damage after tensile stress.